EDUCAÇÃO PROFISSIONAL NO MARANHÃO CONTEMPORÂNEO: consistência e adequação dos cursos do Instituto de Educação, Ciência e Tecnologia do Maranhão (IEMA) face às tendências do mercado de trabalho formal maranhense - SOUSA, Paulo Roberto Correia (2020)
This dissertation analyzes the consistency and adequacy of High School technical courses offered by the Institute of Education, Science and Technology of Maranhão (IEMA) in face of the trends of formal job market in Maranhão. To this end, based on bibliographic, documentary research and analysis of secondary data, it addresses the debate about the current process of productive restructuring and its impacts on the requirements of professional qualification and on employment. The historical and structural determinants of professional education in Brazil since the colonial period are presented, with emphasis on the transformations experienced between the second half of the 1990s and the end of the year 2014 and on the contemporary experiences developed in the State of Maranhão. It approaches IEMA in its conception and its institutional design with emphasis on the results obtained in terms of offering courses during the years of study, having as sources of research the official documents of the Institution. It contextualizes the dynamics of Maranhão and Brazilian labor market in the 2000s, in order to discuss the formalization of jobs and the areas of courses offered by IEMA in the face of the demands of Maranhão labor market. With regard to the time frame, despite the Institute having been implemented since 2015, this research extends to the four-year period (2015 to 2018), corresponding to the first term of the Flávio Dino Government.